Expression of hypoxia inducible factor-1α and vascular endothelial growth factor-C in human chronic periodontitis - Qing-Yan Shi; Shi-Guang Huang; Jing-Hua Zeng; Xiao-Guo Fang (Elsevier, 2015)
Background/purpose: Evidence shows that there is a relationship between hypoxia and inflammatory response in periodontitis. Hypoxia-inducible factor (HIF)-1α is a major regulator of energy homeostasis and cellular adaptation to low oxygen stress. Although experimental results demonstrate an association between HIF-1α and vascular endothelial growth factor (VEGF)-C in tumor angiogenesis, the role of HIF-1α and VEGF-C in the pathogenesis of periodontitis is still ambiguous. So far, limited attention has been given to the role of hypoxia and VEGF-C in periodontitis. The present study aimed to investigate the expression and distribution of HIF-1α and VEGF-C in gingival tissue samples from patients with different stages of chronic periodontitis and healthy individuals. Materials and methods: A total of 56 samples were involved in this study, including moderate chronic periodontitis (n = 20), advanced chronic periodontitis (n = 20), and healthy control tissues (n = 16). The gingival specimens were stained with hematoxylin and eosin for histopathology. The expression of HIF-1α and VEGF-C in gingival tissues was detected by immunohistochemical staining. Results: HIF-1α and VEGF-C were found in gingival tissues from patients with different stages of chronic periodontitis as well as healthy control tissues. HIF-1α protein was expressed mainly in the epithelial layer of gingival tissues, and VEGF-C protein was mostly located in the connective tissue papilla of gingival tissues. Compared with healthy controls, the expression of HIF-1α and VEGF-C in chronic periodontitis groups was significantly higher (P < 0.01), and the density of HIF-1α and VEGF-C in advanced chronic periodontitis group was even significantly higher than that in the moderate chronic periodontitis group (P < 0.01). Conclusion: Our results suggest that the expression of HIF-1α and VEGF-C increased with severity of periodontitis. So, we conclude that HIF-1α may play an important role in the pathophysiology of human periodontitis and may be related to the function of VEGF-C during periodontitis.